Problem based learning in aerospace engineering education: case study of MECH 4129 Engineering Lab IV (pre-liminary result) - Pebrianti, Dwi; Bayuaji, Luhur; Mahdiana, Deni; Md Yusof, Hazlina; Ahmad Zabidi, Suriza (Kulliyyah of Engineering, IIUM, 2023)
According to data from the Malaysian Ministry of Education, the number of students enrolled in engineering programs has been steadily increasing over the past few years. Focusing on aerospace engineering, the aerospace industry in Malaysia has been growing steadily over the past few years. Overall, the aerospace industry in Malaysia is currently experiencing growth and development, and is seen as a key area for future economic growth and innovation in the country. However, the feedback from some of Malaysian companies related to students’ performance during their industrial practice, shows that the skill of the students does not meet the companies’ requirement. Most of the students have very good CGPA but when they are given a special task during the industrial training, the students failed to complete the tasks which is related to their skills. To overcome this problem, this study proposed a new technique in teaching delivery, with the case study of subject MECH 4129 Engineering Lab IV, specifically the spacecraft control and guidance part. The delivery is designed to meet the syllabus and give opportunity to the students to learn while doing a small project. Students need to develop a gradient stabilization system as a task to be completed. The system consists of a servo motor, two ultrasonics and an Arduino board as the microprocessor. Students are expected to come out with a prototype to fulfill the task. It shows that by only giving the materials and the task to be completed, students are able to produce different prototypes based on their understanding. At the end of the semester, questionnaire is given to students in order to observed their understanding through the project-based learning. 17 out of 25, about 68% students took participation in answering the questionnaire. Some of the questions given are related to the control system, the understanding of servo motor working principle, the ability to derive mathematical equations from servo motor and ultrasonics sensors and lastly the understanding of PID design for the system. The result shows that there is 20% improvement in the knowledge acquisition, where pre-test average result is 60% and post-test average result 80%. Additionally, the preliminary result shows that students have better motivation, innovation and gain their knowledge, skill and confident that will be useful to face the real engineering world.